2016
DOI: 10.1186/s12872-016-0350-z
|View full text |Cite
|
Sign up to set email alerts
|

Leg edema with (S)-amlodipine vs conventional amlodipine given in triple therapy for hypertension: a randomized double blind controlled clinical trial

Abstract: BackgroundLeg edema is a common adverse effect of dihydropyridine Calcium Channel Blockers (CCB) that may need dose reduction or drug withdrawal, adversely affecting the antihypertensive efficacy. Leg edema is reported to occur less often with (S)-amlodipine compared to conventional racemic amlodipine. We aimed to find the incidence of leg edema as a primary outcome and antihypertensive efficacy with (S)-amlodipine compared to conventional amlodipine.MethodsThis prospective, double-blind, controlled clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
1
17
2
Order By: Relevance
“…19 However, the major limitation with use of amlodipine is the higher incidence of pedal oedema, which is a common adverse effect shared by dihydropyridine CCBs. 20 This was further confirmed in our study where about two-third of physicians observed pedal oedema with amlodipine in their >10% patients. Pedal oedema has also been of concern with newer CCB like cilnidipine; one-third of the physicians observed pedal oedema even with use of cilnidipine.…”
Section: Discussionsupporting
confidence: 83%
“…19 However, the major limitation with use of amlodipine is the higher incidence of pedal oedema, which is a common adverse effect shared by dihydropyridine CCBs. 20 This was further confirmed in our study where about two-third of physicians observed pedal oedema with amlodipine in their >10% patients. Pedal oedema has also been of concern with newer CCB like cilnidipine; one-third of the physicians observed pedal oedema even with use of cilnidipine.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, it has been reported that leg edema is less prevalent with S-amlodipine compared with racemic amlodipine. 20 , 25 In the present study, pretibial edema was determined in 2 patients (one at a dose of 2.5 mg/d and one at a dose of 5 mg/d).…”
Section: Discussionmentioning
confidence: 95%
“…In conclusion, the present study investigated the clinical efficacy of combination treatment with captopril and prazosin in patients with gestational hypertension in a phase-II clinical study. Although previous studies have identified a number of drugs that exhibit direct effects on gestational hypertension, it is important to investigate the overall role of captopril and prazosin in affecting hypertension and hypertension-related indicators (36,37). The clinical outcomes presented that captopril and prazosin revealed novel options in gestational hypertension management and an increasing number of clinical reports demonstrate promising results.…”
Section: Discussionmentioning
confidence: 99%